2021
DOI: 10.55563/clinexprheumatol/ert0p7
|View full text |Cite
|
Sign up to set email alerts
|

Disease characteristics of psoriatic arthritis patients may differ according to age at psoriasis onset: cross-sectional data from the Psoriatic Arthritis-International Database

Abstract: ObjectiveTo explore the impact of early versus late-onset psoriasis (PsO) on the disease characteristics of psoriatic arthritis (PsA) in a large-multicentre cohort. MethodsThe data from a multicentre psoriatic arthritis database was analysed. Patients were grouped according to age at psoriasis onset (early onset; <40 years of age, late-onset; >40 years of age) and disease characteristics of the groups were compared by adjusting for BMI and PsA duration, where necessary. Results At the time of analyses, 1634 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“… 18 To our knowledge, there is no study with similar objectives to ours with psoriasis as a reference. Bilgin et al 19 observed differences in the phenotype of psoriasis without any important impact in terms of PsA in patients with an early onset (<40 years) and late onset (>50 years) of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“… 18 To our knowledge, there is no study with similar objectives to ours with psoriasis as a reference. Bilgin et al 19 observed differences in the phenotype of psoriasis without any important impact in terms of PsA in patients with an early onset (<40 years) and late onset (>50 years) of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…У большей части (73%) пациентов с тяжелыми и средне-тяжелыми формами псориаза, включенных в регистр пациентов с псориазом РОДВК, отмечалось РНП, что согласуется с данными других авторов [1,2,5]. Как и в других исследованиях, пациенты с РНП были моложе и имели бóльшую продолжительность псориаза на момент включения в регистр [2,11,12].…”
Section: Discussionunclassified
“…Схожие результаты по возрасту установления диагноза псориаза (23,5±9,4 и 50,4±7,2 года соответственно) и ПсА (35,8±11,2 и 54,2±8,4 года соответственно) были получены E. Bilgin и соавт. [11].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A recent analysis in PsO patients confirmed that HLA alleles explain a larger heritability of EOP, moving towards a genetic profiling to predict the PsO risk of a more severe phenotype [ 5 ]. The PsO stratification age among PsA patients was also assessed, showing that it could play a role in the clinical and genetic features of PsA patients [ 6 , 7 ]. Furthermore, in PsA patients, LOP was described as an independent cardiovascular disease-associated factor [ 8 ].…”
Section: Introductionmentioning
confidence: 99%